Lateral cephalometry: A simple and economical clinical guide for assessment of nasopharyngeal free airway space in mouth breathers - Navneet Grewal; Alkesh V Godhane (Wolters Kluwer Medknow Publications, 2010)
Nasopharyngeal obstruction by adenoid enlargement is one of the main causes of mouth breathing. Cephalometric radiographs and rhinomanometric tests to evaluate nasal obstruction have been available for several decades. Various lines and areas have been interpreted by number of investigators to implicate the enlarged adenoid in a casual relationship with mouth breathing and the subsequent effect on vertical facial growth. The aim of this paper is to review lateral cephalometric tracing methods combined with newer Auto-cad surface area measurement program so that assessment of the nasopharyngeal free airway space can be done based on it, before more rigorous ear-nose-throat follow up is needed for the patient.